2009
DOI: 10.1021/la803652x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Insights into the Hydrated (10.4) Calcite Surface: Structure, Energetics, and Bonding Relationships

Abstract: Roothaan-Hartree-Fock molecular orbital methods were applied to investigate the ground-state structural, energetic properties, and bonding relationships of the hydrated (10.4) calcite surface. The adsorption of water molecules was modeled at the 6-31G(d,p) level of theory using Ca(n)(CO(3))(n) slab cluster models (4 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 73 publications
10
40
0
Order By: Relevance
“…Surface energies are obtained from DFT computations of hydrated calcium carbonate surface slabs with partial Mg 2+ substitution on calcium sites (SI Appendix, section S.I.6). The solvated surface is modeled by adsorption of explicit water molecules on the cation sites, which physically captures the thermodynamic effect of water hydration (34). The dominant facets of the aragonite nucleus are predicted to be the (001), (011), (010), and (110) forms, and for calcite the ð1014Þ and ð1010Þ forms, consistent with experimental morphologies and other calculations in the literature (35,36).…”
Section: Variation Of Caco 3 Nucleation Barriers With Solution Mg:ca supporting
confidence: 75%
See 1 more Smart Citation
“…Surface energies are obtained from DFT computations of hydrated calcium carbonate surface slabs with partial Mg 2+ substitution on calcium sites (SI Appendix, section S.I.6). The solvated surface is modeled by adsorption of explicit water molecules on the cation sites, which physically captures the thermodynamic effect of water hydration (34). The dominant facets of the aragonite nucleus are predicted to be the (001), (011), (010), and (110) forms, and for calcite the ð1014Þ and ð1010Þ forms, consistent with experimental morphologies and other calculations in the literature (35,36).…”
Section: Variation Of Caco 3 Nucleation Barriers With Solution Mg:ca supporting
confidence: 75%
“…27. Hydrated surface energies were calculated with explicit H 2 O molecules, placed 2.4 Å above each calcium ion (34), oriented with lone-pair orbitals facing the nearest Ca 2+ or Mg 2+ ion and a hydrogen pointed toward the nearest oxygen atom, then relaxed by simulated annealing. The use of H 2 O adsorbates is a reasonable approximation for hydrated surface energies under pH values corresponding to neutral and ocean water (pH = 8.1).…”
Section: Methodsmentioning
confidence: 99%
“…4 doubling the surface unit cell in the b dimension) that has been ascribed to a slight rotation of some surface carbonate groups. While the (2 xl) superstructure on calcite (104) face matches with low energy electron diffraction 122] and computer modelling studies [23,24], it has not been observed by Rode et al [20] using frequency modulation AFM.…”
Section: Resultssupporting
confidence: 72%
“…Calcite surface functional groups of the dominating crystallographic plane (calcite (1 0 4) surface) behave differently than those of oxides, because they are assumed to be controlled by two different types of sites resulting from the hydrolysis of surface water molecules: a hydroxylated calcium cation, >CaOH, and a protonated carbonate anion, >CO 3 H surface site [8,11]. This assumption of hydrolysis of surface water molecules at the calcite-water interface was recently questioned by a theoretical study showing that surface water molecules may not be dissociated and that >CaOH 2 and >CO 3 surface sites may thus control the calcite surface speciation [58]. Following the recent surface complexation model of Heberling et al [10], we will also consider the presence of >CaOH 2 and >CO 3 surface sites at the calcite surface.…”
Section: Calcite Surface Complexation Modelmentioning
confidence: 99%